Equações algébricas no ensino fundamental: um panorama de dissertações da PUC-SP - Pereira, Armando (2010)
The purpose of this research was to develop a panorama of the dissertations from PUC-SP about the theme algebraic equations in Elementary School (6th to 9h grades). The methodology from the essay was defined as having a bibliographic character, in the "panorama" modality. Our analysis method was constituted of four dissertations published, from 2005 to 2008, in the Mathematical Education area. For the essay selection, it was used the site of the Program of Post- Graduate Studies in Mathematical Education from PUC-SP, obeying to predetermined criteria. Thus, the similarities among the purposes, conclusions, indications, for future researches and theoretical referentials were sought. The results indicated that the majority of the researches analyzed presented similarities between the researchers conclusions and the indications for future researches. However, there were very few similarities between the purposes of these researches and between the theoretical referentials used in the development of the dissertations. At last, it is considered to have presented a contribution to the Group of Researches in Algebraic Education from PUC-SP and possibly to the investigation in Mathematical Education, because research modalities of bibliographical type are recognized, not considered before by authors that theorized about them, which it was not our initial intention. Being, this, the present study presented results that might give subsides to future researches